2021
DOI: 10.1038/s41598-021-81176-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiotherapy on survival in advanced hepatocellular carcinoma patients treated with sorafenib: a nationwide cancer-registry-based study

Abstract: Sorafenib is the standard treatment for advanced hepatocellular carcinoma (HCC) patients. This study aims to determine whether combining radiotherapy with sorafenib administration increases its efficacy. The study cohort included 4763 patients with diagnosed advanced HCC who received sorafenib between January 2012 and December 2015, as reported in medical records in the Taiwan Cancer Registry database. The effect of sorafenib with or without radiotherapy on survival was calculated using the Kaplan–Meier method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Ricke et al evaluated the potential impact of the combination of sorafenib and selective yttrium-90 transarterial radioembolization and showed that combination treatment did not improve OS of the patients compared to sorafenib only therapy (112). However, a retrospective study that included 4,763 patients diagnosed with HCC showed improved OS of the patients that underwent radiotherapy within sorafenib use compared to patients that only received sorafenib therapy (113). Moreover, a recent clinical trial demonstrated that a combination of sorafenib, hepatic arterial infusion chemotherapy of oxaliplatin, fluorouracil, and leucovorin, and FOLFOX enhances OS of advancedstage HCC patients compared to individuals who received sorafenib monotherapy (114).…”
Section: Combination Therapy With Sorafenibmentioning
confidence: 99%
“…Ricke et al evaluated the potential impact of the combination of sorafenib and selective yttrium-90 transarterial radioembolization and showed that combination treatment did not improve OS of the patients compared to sorafenib only therapy (112). However, a retrospective study that included 4,763 patients diagnosed with HCC showed improved OS of the patients that underwent radiotherapy within sorafenib use compared to patients that only received sorafenib therapy (113). Moreover, a recent clinical trial demonstrated that a combination of sorafenib, hepatic arterial infusion chemotherapy of oxaliplatin, fluorouracil, and leucovorin, and FOLFOX enhances OS of advancedstage HCC patients compared to individuals who received sorafenib monotherapy (114).…”
Section: Combination Therapy With Sorafenibmentioning
confidence: 99%
“…Liver cancer, one of the most common neoplastic malignancies, is characterized by high incidence, postsurgical recurrence and poor prognosis [ 1 , 2 ]. Hepatocellular carcinoma (HCC) accounts for 70–90% of primary liver cancer, caused a heavy burden of disease on people and is estimated to be the third leading cause of cancer-related death worldwide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 However, these drugs are limited to only patients with preserved liver function and their response rates are unsatisfactory. 15,16 In clinical practice, patients who progress after sorafenib frequently receive local treatments, including TACE and RT, 17 but evidences of their efficacy are lacking.…”
Section: Introductionmentioning
confidence: 99%